Efficient Verifier-Local Revocation for Anonymous Credentials - Bobolz, Jan

Efficient Attributes for Pairing-Based Anonymous Credentials - Stroh, Christian

Dynamics and Efficiency in Topological Self-Stabilization - Koutsopoulos, Andreas

Distributed Data Structures and the Power of topological Self-Stabilization - Kniesburges, Sebastian

Diffusion of Innovations in Social Networks - Kunisch, Christina

Die Wirksamkeit von Zertifikaten als Qualitätssignal - Reimann, Alina

Die Einführung der EU-Merger Guidelines - Effizienz und Wohlfahrtswirkungen - Topal, Barlas

Design of an Evaluation Strategy for Fuzzy Service Matching - Bruns, Melanie

Constructions of Fully Secure Predicate Encryption Schemes - Schleiter, Patrick

Confined Guessing: New Signatures From Standard Assumptions - Böhl, Florian; Hofheinz, Dennis; Jager, Tibor; Koch, Jessica; Striecks, Christoph (J. Cryptology)

On the Security of TLS 1.3 and QUIC Against Weaknesses in PKCS#1 v1.5 Encryption - Jager, Tibor; Schwenk, Jörg; Somorovsky, Juraj (Proceedings of the 22nd ACM SIGSAC Conference on Computer and Communications Security, Denver, CO, USA, October 12-16, 2015)

Practical Invalid Curve Attacks on TLS-ECDH - Jager, Tibor; Schwenk, Jörg; Somorovsky, Juraj (Computer Security - ESORICS 2015 - 20th European Symposium on Research in Computer Security, Vienna, Austria, September 21-25, 2015, Proceedings, Part I)

On the Selective Opening Security of Practical Public-Key Encryption Schemes - Heuer, Felix; Jager, Tibor; Kiltz, Eike; Schäge, Sven (Public-Key Cryptography - PKC 2015 - 18th IACR International Conference on Practice and Theory in Public-Key Cryptography, Gaithersburg, MD, USA, March 30 - April 1, 2015, Proceedings)

One-Round Key Exchange with Strong Security: An Efficient and Generic Construction in the Standard Model - Bergsma, Florian; Jager, Tibor; Schwenk, Jörg (Public-Key Cryptography - PKC 2015 - 18th IACR International Conference on Practice and Theory in Public-Key Cryptography, Gaithersburg, MD, USA, March 30 - April 1, 2015, Proceedings)

Verifiable Random Functions from Weaker Assumptions - Jager, Tibor (Theory of Cryptography - 12th Theory of Cryptography Conference, TCC 2015, Warsaw, Poland, March 23-25, 2015, Proceedings, Part II)

Tightly-Secure Authenticated Key Exchange - Bader, Christoph; Hofheinz, Dennis; Jager, Tibor; Kiltz, Eike; Li, Yong (Theory of Cryptography - 12th Theory of Cryptography Conference, TCC 2015, Warsaw, Poland, March 23-25, 2015, Proceedings, Part I)

Comprehensive Service Matching with MatchBox - Börding, Paul; Bruns, Melanie; Platenius, Marie Christin (10th Joint Meeting of the European Software Engineering Conference and the ACM SIGSOFT Symposium on the Foundations of Software Engineering (ESEC/FSE'15))
Nowadays, many service providers offer software components in the form of Software as a Service. Requesters that want to discover those services in order to use or to integrate them, need to find out which service satisfies their requirements best. For this purpose, service matching approaches determine how well the specifications of provided services satisfy their requirements (including structural, behavioral, and non-functional requirements). In this paper, we describe the tool-suite MatchBox that allows the integration of existing service matchers and their combination as part of flexibly configurable matching processes. Taking requirements and service specifications as an input, MatchBox is able to execute such matching processes and deliver rich matching results. In contrast to related tools, MatchBox allows users to take into account many different kinds of requirements, while it also provides the flexibility to control the matching process in many different ways.

Competition and Product Innovation of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen
On an intermediate goods market we allow for vertical and horizontal product differentiation and analyze the influence of simultaneous competition for resources and customers on the market outcome. Asymmetries between intermediaries cannot arise just from distinct product qualities, but also from different production technologies. The intermediaries face either price or quantity competition on the output market and a monopolistic input supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Considering product innovation for symmetric productivities we derive equilibrium conditions on the investment costs and compare price and quantity competition. It turns out that on the one hand there exist product qualities and degrees of horizontal product differentiation for complements such that asymmetric investment equilibria fail to exist. On the other hand we find that there also exist product qualities and degrees of horizontal product differentiation for substitutes such that existence can be guaranteed if the investment costs are chosen accordingly.

Combining Service-oriented Computing with Embedded Systems - A Robotics Case Study - Jungmann, Alexander; Jatzkowski, Jan; Kleinjohann, Bernd (Proceedings of the 5th IFIP International Embedded Systems Symposium)
In this paper, we introduce an approach for combining embedded systems with Service-oriented Computing techniques based on a concrete application scenario from the robotics domain. Our proposed Service-oriented Architecture allows for incorporating computational expensive functionality as services into a distributed computing environment. Furthermore, our framework facilitates a seamless integration of embedded systems such as robots as service providers into the computing environment. The entire communication is based on so-called recipes, which can be interpreted as autonomous messages that contain all necessary information for executing compositions of services.

Budget Games with priced strategies - Pautz, Jannis